HCI Practices in the Nigerian Software Industry - Ogunyemi, Abiodun; Lamas, David; Adagunodo, Rotimi; Da Rosa, Barreto (Human-Computer Interaction, 2023)
from book Human-Computer Interaction – INTERACT 2015: 15th IFIP TC 13 International Conference, Bamberg, Germany, September 14-18, 2015, Proceedings, Part II (pp.479-488)